Case report and literature review: autonomous robotic system assisted palatal implantation at an anterior teeth site compromised by periapical cyst - Liu, Xiuyu; Lv, Huixin; Chen, Meiqing; Chen, Siyu; Jia, Kewen; Quni, Sezhen; Zhang, Lu; Zhou, Yanmin (Frontiers in Medicine, 2024)
Background: Immediate Implant Placement (IIP), which preserves gingival height and papilla shape while simultaneously accelerating the implant treatment period, has become a popular method due to its commendable clinical outcomes. Nonetheless, deploying immediate implants in aesthetic areas demands specific preconditions concerning the remaining alveolar bone. This poses a challenge to the accuracy of implant surgery.In this report, we present the case of a 60-year-old woman with a left upper anterior tooth crown dislodged for over a month. Cone Beam Computed Tomography (CBCT) revealed the absence of a labial bone wall on tooth 22, a remaining 1mm bone wall on the labial side of the root apex, and a 17.2 mm*8.9 mm*4.7 mm shadow in the periapical region of the root apices of teeth 21 and 22, with the narrowest width on the sagittal plane being approximately 5 mm. After the surgeon removed the cyst, they completed the subsequent implantation surgery using an autonomous robot in a challenging aesthetic area. This method circumvented the potential exposure of the screw thread on the labial implant surface, assured initial implant stability.Five months after the operation, the dental crown was restored. The implant remained stable, with yielding notable clinical results. To the best of our knowledge, this clinical case is the first to report the feasibility and precision of immediate implantation in anterior teeth sitein an aesthetic area with periapical cyst removal, performed by an autonomous robotic surgical system. Autonomous robots